Profitabilitas, Leverage, Kebijakan Dividen, Kepemilikan Institusional dan Growth terhadap Nilai Perusahaan - Tri Purwani; Okta Oktavia (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2018)
The purpose of this study is to examine the influence of profitability, leverage, dividend policy, institutional ownership and company growth on firm value. This study population comprised the manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2016 with a total of 469 companies. Sampling were taken by using purposive sampling technique. Based on specified criteria were acquired 18 companies. The collected data was analyzed by using multiple linear regression. The results of rearch show that the variables of profitability, leverage, dividend policy and growth have a positive and significant effect on the firm value, while the institutional variable of ownership has a negative and significant effect on the firm value. This means that institutional ownership has not been able to be the right mechanism for increasing the firm value.